Analysis and investigation of the leakage failure on the shale gas gathering and transmission pipeline. (October 2022) - Tong, Ke; Bai, Xiao-liang; Fan, Zhi-hai; Cheng, Liao; LYU, Jian-jun; Han, Xin-li; Qu, Ting-ting
Highlights: A rare accident that a shale gas gathering and transportation pipeline suffer corrosion and leakage within less than 10 months was investigated and analyzed. The corrosion behavior, corrosion types and corrosion mechanism of shale gas pipelines are studied. Effective measures to prevent corrosion of shale gas gathering and transportation pipelines in this area are proposed. After improvement, the shale gas pipeline has been running safely and stably so far. Abstract: There is an accident that a shale gas gathering and transportation pipeline suffer corrosion and leakage within less than 10 months of its operation, which is rare for pipelines to have corrosion faults in such a short time. In this paper, through a series of experiments such as macroscopic observation, wall thickness measurement, physical and chemical inspection, optical microscope (OM), scanning electron microscope (SEM) as well as energy dispersive spectrometry techniques (EDS), the failed pipeline was analyzed, and subsequently the water quality analysis and bacterial counts were performed on the gas field produced water in the transmission medium. Consequently, according to the experimental results and field investigation, the root cause was identified that the failure mode of seamless steel pipe was corrosion leakage caused by local corrosion. The main reason for corrosion and leakage is that the metal on the inner wall of the pipeline is first corroded by sulfate-reducing bacteria (SRB) in the transmission medium, and a layer of black corrosion biofilm is deposited at the bottom of the steel pipe. If the corrosion biofilm has defects such as damage, the exposed metal and black corrosion biofilm will form the electrode corrosion with large cathode and the small anode, which will accelerate the corrosion rate and eventually lead to rapid corrosion failure of steel pipe. For the purpose of avoiding similar accidents, suggestions to prevent such failures were proposed in this paper.